2021
DOI: 10.26682/ajuod.2021.24.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iba And Media on Rooting Percentage And Growth of Semi-hardwood Cuttings of Red-tip Photinia Plant (photinia X Fraseri)

Abstract: Experiment was carried out in plastic house that belong to the Red Rose Nursery / Dohuk government in autumn season between 1 st Oct 2018, to 30 th May 2019, to discuss the effect of media ( peat moss, sand and peat moss+ sand), & IBA concentrations (0, 4000, 6000, 8000) mg.l -1 on rooting might of Semi-hardwood cuttings of photinia (Photinia x fraseri) plant. Results indicate that the highest rooting percentage (50.88) %, plant high (19.17) cm, vegetative fresh weight (9.10) gm and vegetative dry weight (4.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In our study, both Kelpak ® and Goteo ® negatively affected root length, surface area and diameter compared to IBA and the control (Table 4). On the contrary, positive effects of Goteo ® on rooting were reported for Physocarpus opulifolius [75], Hydrangea paniculata [90], Ornithogalum arabicum [91] and rose [58]. In Fraser's Photinia, both Kelpak ® and Goteo ® at different concentrations decreased the number of root tips, forks and crossings compared to the IBA treatment (Table 5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, both Kelpak ® and Goteo ® negatively affected root length, surface area and diameter compared to IBA and the control (Table 4). On the contrary, positive effects of Goteo ® on rooting were reported for Physocarpus opulifolius [75], Hydrangea paniculata [90], Ornithogalum arabicum [91] and rose [58]. In Fraser's Photinia, both Kelpak ® and Goteo ® at different concentrations decreased the number of root tips, forks and crossings compared to the IBA treatment (Table 5).…”
Section: Discussionmentioning
confidence: 97%
“…For example, refs. [57,58], have achieved the best results with 0.8%, while Bonamino and Blazich [49] have applied IBA at 1%. Kelpak ® (identified as K), is composed of 34% (w/w) E. maxima extract 11.16 mg L −1 auxin and 0.031 mg L −1 cytokinin (with a auxin:cytokinin ratio of 360:1), alginates (1.5 L −1 ), amino acids (total 441.3 mg 100 g −1 ), mannitol (2261 mg L −1 ), neutral sugars (1.08 g L −1 ), and small amounts of macroelements (N 0.09%, P 90.7 mg kg −1 , K 7163.3 mg kg −1 , Ca 190.4 mg kg −1 , Mg 337.2 mg kg −1 , Na 1623.7 mg kg −1 ) and microelements (mean composition: Mn 17.3 mg kg −1 , Fe 40.7 mg kg −1 , Cu 13.5 mg kg −1 , Zn 17.0 mg kg −1 , B 33.0 mg kg −1 ) [43,59].…”
Section: Rooting Promoters and Cutting Propagationmentioning
confidence: 99%
“…Several studies had reported that the effective action in the process of adventitious root formation can be influenced by a series of internal and external factors. Among internal factors, the most important role goes to phytohormones, especially the auxins, is attributed [12,24,25,26,27]. It is generally believed that auxin have a particular role in root initiation [28].…”
Section: Figure (4): Effect Of Cutting Collection Time and Iba Concen...mentioning
confidence: 99%